Analisis Tipe Ideal Birokrasi Dengan Konsep Birokrasi Weber di Kantor Walikota Jakarta Utara - Kusumah, Fitrya Anugrah; Cokro, Mahdavikia; Salsabila, Neisya; Harywibowo, Ryan; Aji, Muhammad Prakoso (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Bureaucracy in Indonesia is often used as a symbol of negligence, slowness, and corruption. inefficient, and partisan in nature, resulting in the emergence of a negative stigma towards the bureaucracy in society which causes further erosion of public trust in the bureaucracy itself. The mayor is a government institution in which there are officials who have different hierarchical positions and authorities. Max Weber explained that a good bureaucracy should be able to fulfill a number of characteristics or what is better known as Weber's ideal type of bureaucracy. In essence, Weber's ideal type of bureaucracy aims for the performance of government institutions to have the principles of efficiency and effectiveness or minimal structure rich in function. This research was conducted to examine the pattern of internal working relationships in the North Jakarta Mayor's Bureaucracy. The research method used is a qualitative approach. Data collection techniques were carried out through interviews, observation and document study methods that were relevant to the researcher's research topic. From the results of this research, it was found that the application of the basic principles of Max Weber's ideal type of bureaucracy which includes work specialization and hierarchy of authority, formalization, recruitment system, career path, and impersonal employee relationships is appropriate so that it can be said that the performance of the North Jakarta Mayor's bureaucrats has met the requirements. as a bureaucracy with minimal structure and rich functions.